Pairing functional connectivity with population dynamics to prioritize corridors for Southern California spotted owls. Issue 5 (3rd February 2021) - Conlisk, Erin; Haeuser, Emily; Flint, Alan; Lewison, Rebecca L.; Jennings, Megan K.
Abstract: Aim: Land use change, climate change, and shifts to disturbance regimes make successful wildlife management challenging, particularly when ongoing urbanization constrains habitat and movement. Preserving and maintaining landscape connectivity is a potential strategy to support wildlife responding to these stressors. Using a novel model framework, we determined the population‐level benefit of a set of identified potential corridors for spotted owl population viability. Location: Southern California, United States. Methods: Combining habitat suitability and dynamic metapopulation models, we compared the benefit of corridors to the Southern California spotted owl population, measured as the increase in the expected minimum abundance, both now and under a future climate. Our approach considered key corridor characteristics important to conservation decisions, namely corridor irreplaceability and local population network benefit. Results: We identified two corridors likely to increase Southern California spotted owl expected minimum abundance under current climate conditions. At the regional scale, of the 27 corridors evaluated, one corridor was irreplaceable (i.e., no other corridors in the network could provide a similar increase in abundance when the irreplaceable corridor was removed) and one corridor was identified as redundant (i.e., remaining corridors in the network can provide some of the increases in abundance offered by the removed corridor). Both putative corridors connected two large, populous and similarly sized patches. Additionally, we identified two more corridors at the local scale. We found that, under climate change, population declines may limit the benefit of connectivity for a range‐restricted species like the spotted owl. Main conclusions: Our analytical approach highlights important criteria for corridor identification and prioritization, namely irreplaceability versus redundancy, local versus regional benefit, and corridor impact in a changing landscape. With the capability of incorporating estimated functional connectivity into population dynamics, our modelling framework advances connectivity decision‐making for other species of conservation concern and archetypal taxa within ecological communities.